Evaluation of the prevalence of hepatitis C virus through rapid test in public health services users in Campina Grande-PB (Research, Society and Development, 2023)
Chronic hepatitis C is a silent evolution disease that can lead to outcomes such as liver cirrhosis and hepatocellular carcinoma (HCC), a public health problem due to high universal morbidity. It is transmitted by single-stranded ribonucleic acid (RNA) virus, discovered in 1989 through studies of contaminated chimpanzees. Unsafe health practices, use of illegal intravenous drugs and tattoos are among the major risk factors for the transmission of this virus. Currently, it is estimated that 71 million people are infected worldwide, in Brazil, the prevalence of 0.7% indicates that 1.032.000 individuals are contaminated. With quick execution and rapid results availability, Rapid Tests (RT) facilitate epidemiological studies and early diagnosis of hepatic impairment, allowing the modification of the natural history of the disease. To evaluate the presence of Anti-HCV antibodies and epidemiological characteristics of hepatitis C in users of health services in Campina Grande-PB. A prospective cross-sectional observational study, from February 2015 to July 2018. Individuals born between 1945 and 1970 who sought health services voluntarily underwent structured questionnaires and the Bioeasy® Rapid Anti-HCV Test. A total of 385 individuals were studied, with a prevalence of Anti-HCV antibodies of 1.84% (n = 7). Of the interviewees, the majority (29.7%) were in the age group between 45 and 50 years and 67.7% were female. Intravenous illicit drug use, tattooing and male sex presented the highest statistical relevance as a risk factor in the study population. A prevalence higher than that estimated for the country was found, which highlights the need to implement strategies aimed at the early detection of virus carriers.